Information Literacy Skills (ILS) as Determinants for Information Search (IS) by Students: Insights From Edo State College of Nursing Sciences (EDOCNS) - Erikume, Progress; Eromosele, Peace Osemudiamen (International Journal of Knowledge Content Development & Technology, 2025)
The study examined information literacy skills in information search by Students in EDOCNS. The study undertook a cross-sectional design using quantitative research. The population of the study is 637 students in EDOCNS. A stratified random sampling technique was used to select 245 participants, consisting of 120 Nursing students and 104 students in Midwifery departments. A structured questionnaire was used to collect data, and copies were administered to 245 students; 204 copies were filled out and found usable. Frequency, mean, and Standard deviation were used for data analysis, and Pearson Product Moment Correlation was used to test the null hypotheses at the 0.05 significance level. The study revealed that students acquire ILS through library orientation and are highly skilled at surfing the Internet for needed information. On average, students have moderate ILS and mostly search for information for assignments and coursework, but inadequate time to search for the right information sources was the major barrier to using ILS for information search. The study was able to show the relationship between students’ age, information search, and Information Literacy Skills in Edocns.